Common practices of Speech and language pathologists about partner oriented training to treat aphasia - Fazaila Ehsaan; Nazia Mumtaz (Journal of the Pakistan Medical Association)
Objective: To find the common practices among speech language pathologists regarding partner-oriented training for aphasic patients.